Analisis Timbulan dan Karakteristik Komposisi Sampah di Bagian Tengah Sungai Ciliwung - Fadilla Ayu Fauzia; Alloysius Pamurda Dhika M; Mahendra Mahendra; Evi Anggraheni; Jeanette Chriselda Haulussy; Nicolas Bernier; Mochamad Adhiraga Pratama (Fakultas Teknik, 2023)
AbstractOne of the causes of river pollution is the presence of waste in water bodies which causes substantial water quality deterioration. The Ciliwung River is one of Indonesia's most polluted rivers with a very high level of pollution. This study aimed to estimate the amount of daily waste generation in water bodies and theircomposition characteristics. Waste samples were taken from segment 4 of Ciliwung River, namely Jalan Juanda Depok. The waste collection method uses a trawl boom and a trap net. The results showed that the average daily waste generation in the Ciliwung River is 323.87 kg/day (standard deviation of 366 kg/day), with the composition of waste dominated by organic waste as much as 68.63%, plastic waste 15.54%, textile waste 10.89%, and other waste 4, 54%. Fluctuating composition results may be caused by weather, sampling locations, and surrounding activities. The average waste generation in Ciliwung River in theliterature is 970 kg/day. The difference in estimates is because 33 illegal waste collection points along segments 5 and 6 of the Ciliwung River are suspected of leaking into the water body. The difference in estimates is also influenced by the percentage of unmanaged waste in DKI Jakarta which was about 0.9%.Keywords: waste generation, waste composition, trawl boom, Ciliwung, waste collection